Gas Hydrate-Based CO2 Separation Process: Quantitative Assessment of the Effectiveness of Various Chemical Additives Involved in the Process - Dashti, H.; Lou, Xia (Springer, 2018)
Gas hydrates technology has been considered as an alternative method for carbon dioxide (CO2) separation. A wide range of studies have been reported in the past decade on the improvement of the separation ef?ciency by using chemical additives. While most of these studies have shown improved kinetics, thermodynamics and/or separation ef?ciency at the laboratory scale, there has been no quantitative analysis of the energy consumption for viable industrial applications. Comparison of the effectiveness of the chemical additives from separate studies or groups also is impossible. The present work is focused on the modelling of the hydrate-based CO2 separation process and provides a quantitative approach that is new in its analysis of the effectiveness of chemical additives in relation to the energy required and the kinetic parameters involved in the process.